The effects of water stress on mung bean (Vigna radiata L.): variability in the growth, biomass & stomatal opening - Yap, Chee Kong; MIM, Hadir; NA, Bakar; SC, Toh; AY, Hafizan; AE, Norazan; D, Ahsani; FNF, Rahim; NA, Rafiyan; NA, Zahrilail; EYI, Hifnei; MA, Ramlee; et al. (Medwin Publishers, 2024)
Mung bean (Vigna radiata) is widely cultivated across Asia and has gained popularity in various cuisines due to its high nutritional value. Rich in protein, dietary fiber, minerals, vitamins, and bioactive compounds like polyphenols and peptides, mung beans are considered a valuable functional food. The present experiment aimed to study the effects of water stress on the growth and yield of mung beans by applying varying water treatment volumes (20, 30, 40, 50, and 60 ml). Key growth parameters measured included stomata size on the stem and leaves, the number of leaves, average plant height, and biomass, all assessed after one week of growth. Water was supplemented every two days, and progress was monitored over the course of the week. The study found that the different volumes of water had a significant impact on the growth patterns, leaf count, biomass, and stomatal opening in the stem and leaves of the mung beans. The results suggest that while an adequate amount of water is essential for maximizing mung bean yield, excessive water can hinder growth by disrupting nutrient balance and other physiological processes. Therefore, to achieve optimal growth and yield in mung beans, careful management of water supply is crucial.